1974
DOI: 10.1172/jci107845
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Proinsulin with Insulin Receptors on the Plasma Membrane of the Liver

Abstract: The interactions of proinsulin with the insulin-specific receptors were investigated in purified rat liver plasma membranes. These studies were de- (1) and the elucidation of its amino acid sequence (2) investigators have performed studies both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
45
1
2

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 33 publications
11
45
1
2
Order By: Relevance
“…Proinsulin, which has 5-10% of the biologic activity of insulin (31), is removed by the isolated perfused rat liver 10-15 times less rapidly than insulin (7). These figures correlate with the known binding of proinsulin to hepatic insulin receptors, which is 5-10% of that for insulin (32). C-peptide, which exerts no biologic activity in the liver, is not metabolized by this organ (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…Proinsulin, which has 5-10% of the biologic activity of insulin (31), is removed by the isolated perfused rat liver 10-15 times less rapidly than insulin (7). These figures correlate with the known binding of proinsulin to hepatic insulin receptors, which is 5-10% of that for insulin (32). C-peptide, which exerts no biologic activity in the liver, is not metabolized by this organ (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…The work of Mortimore and Tietze with cyclically perfused rat livers suggested that insulin degradation required prior "capture" and transport to a presumed intracellular degrading site (3). Stoll et al (4) and Rubenstein,et al (5) have shown that proinsulin, which has relatively low biological potency (6,7) and which binds poorly to rat liver plasma membranes (8), is extracted very slowly by the isolated perfused liver. In addition, Csorba, et al (9) have shown that 'I-desalanyl-desasparaginyl insulin, an analogue with very low biological potency (10)(11)(12)(13)(14), which inhibits the binding of 'I-insulin to insulin receptors only at relatively high concentrations (10)(11)(12)(13)(14)(15), is removed more slowly from the plasma of dogs than 'I-insulin in a comparable dose.…”
Section: Introductionmentioning
confidence: 99%
“…METHODS Materials. The rat and human insulins, 20 (28); monoiodinated insulin, 380 uCi/jsg (29); and monoiodinated-proinsulin, 250 /Ci/,g (30) were labeled by the chloramine-T method (31). L-[4,5-'H]leucine (40 Analytical grade anion-exchange resin (AGI-X2) was from Bio-Rad, (Paris).…”
Section: Introductionmentioning
confidence: 99%